2009
DOI: 10.1016/j.jsb.2009.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Structure of first- and second-stage mineralized elements in teeth of the sea urchin Lytechinus variegatus

Abstract: Microstructure of the teeth of the sea urchin Lytechinus variegatus was investigated using optical microscopy, SEM (scanning electron microscopy) and SIMS (secondary ion mass spectroscopy). The study focused on the internal structure of the first-stage mineral structures of high Mg calcite (primary, secondary and carinar process plates; prisms) and on morphology of the columns of second-stage mineral (very high Mg calcite) that cement the first-stage material together. Optical micrographs under polarized light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…4F and G) and an EDS line scan through this region reveals that the core material is in fact organic, suggesting that it may play an important templating role during the formation of each needle during tooth growth and maturation. While the presence of this organic core had been suggested previously based on results obtained from X-PEEM (Killian et al, 2009(Killian et al, , 2011Ma et al, 2009), secondary electron (Brear and Currey, 1976;Ma et al, 2007;Robach et al, 2009;Veis et al, 2002;Wang, 1998), traditional 8-bit BS-SEM (Killian et al, 2011), and optical microscopy (Giesbreclit, 1880;Robach et al, 2009;Salter, 1860) imaging studies, 16-bit BS-SEM provides a clear, high contrast verification of its existence and EDS line scanning confirms its organic composition.…”
Section: Resultsmentioning
confidence: 69%
“…4F and G) and an EDS line scan through this region reveals that the core material is in fact organic, suggesting that it may play an important templating role during the formation of each needle during tooth growth and maturation. While the presence of this organic core had been suggested previously based on results obtained from X-PEEM (Killian et al, 2009(Killian et al, , 2011Ma et al, 2009), secondary electron (Brear and Currey, 1976;Ma et al, 2007;Robach et al, 2009;Veis et al, 2002;Wang, 1998), traditional 8-bit BS-SEM (Killian et al, 2011), and optical microscopy (Giesbreclit, 1880;Robach et al, 2009;Salter, 1860) imaging studies, 16-bit BS-SEM provides a clear, high contrast verification of its existence and EDS line scanning confirms its organic composition.…”
Section: Resultsmentioning
confidence: 69%
“…One question is whether the second stage grows epitaxially on the pre-existing first stage mineral. Numerous studies have shown that very high Mg calcite columns nucleate at many different locations between adjacent first stage plates or prisms and that the two phases are in contact or, at a minimum, are separated by a very thin layer of organic material (10). If the two crystal phases are in direct contact, the case would very strong for an epitaxial relationship, albeit with an incoherent interface.…”
Section: Discussionmentioning
confidence: 99%
“…All form in spaces between cellular syncytia. The second stage fills the space between adjacent first stage mineral elements (2,6–10). Like their names imply, the first stage mineral elements develop initially in the plumula (most aboral portion of the tooth) and the second stage mineral (in the form of columns or disks) subsequently links the plates and prisms together.…”
Section: Introductionmentioning
confidence: 99%
“…The impressive ability of sea urchin tooth is certainly related to the structure of the whole tooth and especially the organization of the materials that make up the mature end, that is, the grinding tip of the tooth. The sea urchin tooth has been investigated extensively in order to understand the unique structural features that enable it to function so effectively as a grinding tool in the past 60 years [6][7][8][9][10][11][12][13]. The major structural elements of the sea urchin tooth are single crystalline primary plates and needles composed of low Mg calcite (5-13 mol% Mg) and Mg-enriched calcite (40-45 mol% Mg) polycrystalline matrix confined to the stone part of the tooth.…”
Section: Introductionmentioning
confidence: 99%
“…Since the biomineralization process is strongly related to the proteins in the biominerals, Veis et al have done a lot of work on the extraction, purification, and analysis of the proteins in the sea urchin tooth in the recent years [8,11,13,15]. Mann et al identified 138 proteins in the matrix of tooth powder, which is the most comprehensive list of sea urchin tooth matrix proteins available at present [16].…”
Section: Introductionmentioning
confidence: 99%